Examining Entrepreneurial Success Factors of Women-Owned SMEs in Rattan Craft - Sanjaya, Deny Wirawan; Kempa, Sesilya (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
The rattan craft industry is one of the most significant contributors to the economy, and women own this business. However, the success of the rattan craft SME is influenced by internal and external factors. This study aims to determine the effect of the personal aspects, environmental aspects, and government support on entrepreneurial success in rattan craft SME women. Data collection was carried out using a questionnaire. The sample used was 100 women SME owners of rattan craft. The sampling technique in this study is to use the accidental sampling technique. The analytical method used is multiple linear regression analysis (SPSS). The results showed that personal and environmental aspects, as well as support from the government, determine the success of rattan craft SMEs that belong to women entrepreneurs. The most considerable influence is from the personal aspect, in which family background and support play an essential role.